2001
DOI: 10.1038/sj.onc.1205027
|View full text |Cite
|
Sign up to set email alerts
|

Transcript map and complete genomic sequence for the 310 kb region of minimal allele loss on chromosome segment 11p15.5 in non-small-cell lung cancer

Abstract: Molecular, functional, and clinical analyses strongly suggest that chromosome segment 11p15.5 contains a gene involved in lung cancer pathogenesis. The critical region of allele loss is 310 kb in size. We used our contig of P1-phage arti®cial chromosome (PAC) clones together with newly identi®ed bacterial arti®cial chromosome (BAC) clones and the draft human genome sequence to complete a contiguous string of 380 407 bp. Three PAC clones that span the region were used to identify transcripts by exon trapping. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
(39 reference statements)
1
25
0
Order By: Relevance
“…The 11p15.4 region, in which the PRKCDBP gene is located, undergoes frequent allelic losses in a variety of human malignancies including breast, lung, and gastric cancer (19)(20)(21)(22). Therefore, PRKCDBP was predicted as a target of deletion in many cancer types displaying frequent LOH at 11p15.4, and allelic loss of the gene was suggested as a plausible mechanism underlying its low expression in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 11p15.4 region, in which the PRKCDBP gene is located, undergoes frequent allelic losses in a variety of human malignancies including breast, lung, and gastric cancer (19)(20)(21)(22). Therefore, PRKCDBP was predicted as a target of deletion in many cancer types displaying frequent LOH at 11p15.4, and allelic loss of the gene was suggested as a plausible mechanism underlying its low expression in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosomal region 11p15 shows frequent deletion in many types of human cancer, including breast, lung, and bladder cancers (1,19,20) In particular, 11p15.5-p15. 4, in which the PRKCDBP gene is located, is a critical region of loss of heterozygosity (LOH) for chromosome 11 in several cancers, suggesting that PRKCDBP might be a target tumor suppressor gene in this region (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…One of the genes in the deleted region is RRM1 (Pitterle et al, 1999;Zhao and Bepler, 2001), and stable expression of a biologically Figure 5 Balb/c mice were subcutaneously injected at a single site with the syngeneic lung adenocarcinoma cell line Line1 and the two transgene-carrying cell lines Line1-Ct and Line1-R1. These lines had been stably transfected with the in-frame (Line1-R1) and outof-frame (Line1-Ct) human RRM1 cDNA constructs.…”
Section: Discussionmentioning
confidence: 99%
“…We also recently reported the completed sequence and transcripts from this region (GenBank Accession numbers AF 391283-5), and that patients with resected stage I NSCLC and allele loss had a survival similar to resected stage II patients (Zhao andBepler, 2001, Bepler et al, 2002). Together, these results suggested that this region contains a gene involved in the regulation of metastasis formation.…”
Section: Introductionmentioning
confidence: 99%
“…RRM1 also acts as a putative tumor suppressor and has been identified within the centromeric part of chromosome segment 11p15.5 . This region, called LOH11A, is frequently lost in NSCLC; it has been completely mapped and sequenced (Zhao and Bepler, 2001), and loss of heterozygosity in this region has been shown to be highly predictive of poor survival in resected NSCLC patients (Bepler et al, 2002). RR overexpression was related to gemcitabine resistance in human oropharyngeal epidermoid carcinoma KB cells (Goan et al, 1999).…”
mentioning
confidence: 99%